Pengecekan Bit Error Pada Media Transmisi Pengiriman Gambar Menggunakan Metode Hamming Code - Deli Alvinda; Achmad Fauzi; Husnul Khair (Bulletin of Multi-Disciplinary Science and Applied Technology, 2022)
The successful delivery of information from the sender (transmitter) to the receiver (receiver) is one thing that is very important in determining the reliability of a communication system. In the world of communication, both communication using cables or using air as a transmission medium will inevitably experience disturbances in the communication process caused by a disturbance called noise. Noise is an unwanted electrical signal. The addition of this unwanted signal in a communication process is a major limiting factor in data communication systems. In the process of data communication, the possibility of data errors received can occur because the data becomes an error and must be re-sent. Hamming code is an error detection method that is able to detect several errors, but is only able to correct one error (single error correction). This error detection method is very suitable for use in situations where there are several random errors.